AN ANALYSIS OF CRITICAL SLOPES STABILITY IN BENDOSARI VILLAGE, PUJON, MALANG DUE TO THE EFFECT OF RAINWATER INFILTRATION - Nindia Rizky Ismawan; Eko Andi Suryo; Arief Rachmansyah (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
A disaster is an incident which threatens and disrupts life. This research was purposed to determine the critical slope stability in Bendosari Village, Pujon due to rainwater infiltration. This research was conducted through ground laboratory test to investigate the type and characteristic of the soil, which then followed by testing of the geo-electric and topography to investigate the existing condition and the ground water level on the critical slopes and analyzed safety factor (SF) using SLOPE/ W for slope with rainwater infiltration effect. The analysis results proved that rainwater infiltration in both conditions could reduce the SF (Safety Factor) value. This is because the water content in the soil increased the pore water pressure. In addition, high water content in the soil reduced the soil shear strength